Physico-mechanical properties of asphalt concrete based on road bitumen modified by rapeseed oil epoxide - Nykypanchuk, Mykhailo; Hrynchuk, Yurii; Olchovyk, Mykola (Видавництво Львівської політехніки, 2013)
The investigation results of type B fine asphalt concrete and its form modified by rapeseed oil epoxide are represented. The efficiency of ERO addition and its positive effect on the physico-mechanical properties of asphalt concrete has been established.
Keywords: asphalt concrete; modifier; epoxide; bitumen; strength; water resistance